Religious Reputation Culture: A Community Based Tourism Development Approach - Windi NR Wardhani; Mochamad Purnomo (Universitas Wahid Hasyim Semarang, 2022)
Abstract The key to a thriving tourism industry is addressing how tourism can benefit society by increasing economic opportunities, supporting socio-cultural systems, and maintaining healthy ecosystems on which communities depend. The tourism industry can no longer focus solely on “how many” tourists visit a destination, or even “how much” money spent at one destination, as a measure of success. Sustainability can be effective if it is carried out by taking time and sustainable efforts, as well as adapting to changes that occur. In this study, the concept of historical heritage tourism and Resource-Based View is used which shows that culture and corporate reputation are seen as very valuable intangible assets. Historical heritage tourism is the key to sustainability. The development of intangible cultural heritage (ICH) is very important for the sustainable development of tourism because historical tourism products can reflect historical values and stories while meeting the emotional needs of tourists.This study aims to explore a new approach in improving sustainable tourism destination development centered on the concept of religious reputation culture. Religious reputation culture is a set of structures, routines, rules, and norms that guide and limit behavior that distinguishes members of one organization from another and is used as a collective perception and assessment of the good name of a tourism destination.The new concept of religious reputation culture plays an important role when an organization engaged in the tourism industry is faced with a change in new habits. The contribution of this research is mainly to the study of reputation and religiosity that when a destination is faced with a different condition, tourists will look for a reputable destination. The pandemic condition encourages tourists to be more aware with a reputation that is halal, thoyib and safe. With the phenomenon of tourism 4.0 accompanied by tremendeous changes in costumer megashifts, tourist destinations must be able to explore and exploit existing knowledge to form a culture of religious reputation as the main capital in carrying out innovation strategies carried out by destinations in order to achieve sustainable destination performance. With a religious reputation culture, the Indonesian’s reputation as a safe, comfortable and competitive tourism destination needs to be continuously developed through various means, so that a positive image will continue to be raised and widely informed, to encourage tourists to have interest and motivation to visit Indonesia. Key word :Religious Reputation Culture; Sustainable Tourism Development; Community Based Tourism